THE DYNAMICS OF AGRARIAN POLICY AFTER THE TRANSMIGRATION PROGRAM: A STRUCTURAL APPROACH AND ITS IMPLICATIONS INNORTH GORONTALO REGENCY - Kusno Katili; Arifin Tahir; Zuchri Abdussamad; Yanti Aneta (Adisam Publisher, 2025)
The objective of this study is to analyze the dynamics of agrarian reform policies in post-transmigration program locations in North Gorontalo Regency using a structural approach and evaluating various indicators that influence the success of its implementation. Data was collected through in-depth interviews, field observations, and policy document analysis. The collected data were analyzed using thematic analysis techniques to identify key issues and the relationships between factors affecting the successful implementation of agrarian policies in post- transmigration areas. The findings indicate that, despite the significant potential of agrarian reform policies in post-transmigration locations to improve the welfare of transmigrants, their implementation remains hindered by several substantial structural issues. The primary challenges identified include inadequate infrastructure, unclear land ownership, a lack of legal certainty regarding land rights, and weak regulatory oversight. An evaluation of income distribution reveals that the program has not yet achieved its intended goal of equitable distribution due to infrastructural challenges and land tenure uncertainties. The complexity of land ownership and tenure security is further compounded by bureaucratic inefficiencies and legal uncertainties. The limited availability of infrastructure and support facilities also constrains transmigrants' ability to enhance their livelihoods. Additionally, weak regulatory enforcement exacerbates policy implementation challenges, as poor coordination among institutions and inconsistent law enforcement hinders the program's effectiveness. This article posits the necessity for policy enhancements, encompassing enhanced planning, bureaucratic simplification, and augmented oversight capacity. These measures are intended to ensure the effective functioning of agrarian policies in post-transmigration regions, thereby achieving their objective of fostering sustainable welfare for both transmigrants and local communities.